2009
DOI: 10.1002/pssa.200880911
|View full text |Cite
|
Sign up to set email alerts
|

Nitride‐based quantum structures and devices on modified GaN substrates

Abstract: We have studied the properties of InGaN layers and quantum wells grown on gallium nitride substrates with intentional surface misorientation with respect to its crystalline c‐axis. Misorientation varied in the range from 0 up to 2 degree. The indium content was changed by using the different growth temperature (between 750 °C and 820 °C) during metalorganic vapor phase epitaxy. With increasing misorientation angle the average indium content decreased significantly. This effect was accompanied by the strong inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…In our previous paper [13], we reported a smaller indium incorporation into the InGaN layers grown on misoriented substrates, as well as larger FWHM of PL peak for those samples, despite smaller indium content in the layers. CL studies showed higher indium incorporation on terraces than at steep stepbunched terrace edges.…”
Section: Indium Incorporation Versus Gan Substrate Misorientationmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous paper [13], we reported a smaller indium incorporation into the InGaN layers grown on misoriented substrates, as well as larger FWHM of PL peak for those samples, despite smaller indium content in the layers. CL studies showed higher indium incorporation on terraces than at steep stepbunched terrace edges.…”
Section: Indium Incorporation Versus Gan Substrate Misorientationmentioning
confidence: 95%
“…The application of such misoriented substrate has an advantage of higher hole concentration [12] and better morphology, but lower indium incorporation [13].…”
Section: Introductionmentioning
confidence: 99%
“…3 However, very few reports on the effects of offcut of bulk GaN substrates on subsequent epitaxy exist in the literature, and these are primarily concerned with the growth of InGaN as compared to AlGaN. 4,5,6 This work aims to elucidate the effect of the surface offcut on the compositional and electrical performance of AlGaN/GaN heterostructures on bulk GaN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] All the experiments described in those references were performed using different homogeneous GaN substrates with different vicinal angles. In this work, we show that the different vicinal angles could be realized within one patterned substrate.…”
mentioning
confidence: 99%